Salt Bladders in Atriplex Spp. - Rajput, Pramila; Sen, David N (Annals of Arid Zone, 2016)
Salt accumulation in bladder cells is the primary means of salt exclusion in Atriplex spp., before it reaches a toxic level in the cell sap. Comparative studies of salt bladdas in A. holocarpa F. Muell. and A. vesica ria Heward ex. Benth. showed differences in the number of stalk-cells and size of the bladders. Bladder structure in young leaves of both species is similar but the variations occur more in the older leaves.